Efficient Photon Extraction in Top-Emission Organic Light-Emitting Devices Based on Ampicillin Microstructures - Kim, Dong Hyun (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.